Maternal Grand Multiparity and the Risk of Severe Mental Disorders in Adult Offspring. - Marius Lahti; Johan G Eriksson; Kati Heinonen; Eero Kajantie; Jari Lahti; Kristian Wahlbeck; Soile Tuovinen; Anu-Katriina Pesonen; Maiju Mikkonen; Clive Osmond; Katri Räikkönen (PLoS ONE, 2014)
BACKGROUND:Previous studies have shown that maternal grand multiparity may predict an increased risk of mental disorders in young adult offspring, but whether such effects persist throughout adulthood remains unknown. The current study examined if maternal grand multiparity predicts the risks of severe mental disorders, suicides, suicide attempts and dementias throughout adult life. METHODS:Our study sample comprised 13243 Helsinki Birth Cohort Study 1934-1944 participants (6905 men and 6338 women). According to hospital birth records, 341 offspring were born to grand multiparous mothers. From Finnish national hospital discharge and causes of death registers, we identified 1682 participants diagnosed with mental disorders during 1969-2010. RESULTS:Maternal grand multiparity predicted significantly increased risks of mood disorders (Hazard Ratio = 1.64, p = 0.03), non-psychotic mood disorders (Hazard Ratio = 2.02, p = 0.002), and suicide attempts (Hazard Ratio = 3.94, p = 0.01) in adult offspring. Furthermore, women born to grand multiparous mothers had significantly increased risks of any severe mental disorder (Hazard Ratio = 1.79, p = 0.01), non-psychotic substance use disorders (Hazard Ratio = 2.77, p = 0.02) schizophrenia, schizotypal and delusional disorders (Hazard Ratio = 2.40, p = 0.02), mood disorders (Hazard Ratio = 2.40, p = 0.002), non-psychotic mood disorders (Hazard Ratio = 2.91, p<0.001), and suicide attempts (Hazard Ratio = 5.05, p = 0.01) in adulthood. The effects of maternal grand multiparity on offspring psychopathology risk were independent of maternal age and body mass index at childbirth, and of year of birth, sex, childhood socioeconomic position, and birth weight of the offspring. In contrast, no significant effects were found among men. CONCLUSIONS:Women born to grand multiparous mothers are at an increased risk of severe mental disorders and suicide attempts across adulthood. Our findings may inform the development of preventive interventions for mental disorders.